Validating a Model of Organizational Culture for Pesantren in South Sumatra: A Structural Equation Modeling Approach - Dahlan, Budi Satriadi Samsul; Othman, Azam; Ibrahim, Mohd Burhan Bin; Shohib, Muhammad Wildan (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2024)
This study aims to validate and confirm the structural modeling (hypothesis model) of organizational culture in Pesantren educational institutions in South Sumatra Province. This study uses a quantitative survey method to collect 420 teachers in Pesantren Educational Institutions in South Sumatra Province using a five-point Pesantren Organizational Culture scale. To understand the respondents' views on organizational cultural factors that affect the quality of education, the researcher used descriptive allegory techniques as well as confirmatory factor analysis and full-fledge SEM. The findings of the study show that teachers in Pesantren educational institutions who are sampled have a high tendency and enthusiasm to practice organizational culture in their respective workplaces. The results of this study have been tested by using SEM on the observed instruments, and the organisation culture model is hypothesized to be empirically valid and reliable. This finding makes an extraordinary contribution to Pesantren educational institutions and top management to intensify the implementation of organizational culture in the Pesantren environment. The findings of this study will help the government, in this case, the minister of education, policymakers, Pesantren management, and education practitioners to support the strategies used in improving the quality of Pesantren educational institutions. This research also ensures the quality of education, especially Islamic education based on Pesantren, by improving culture and organizational performance. This study has successfully tested, formulated, and validated the organizational culture hypothesis model for Pesantren in South Sumatra Province.